Design, Development, and Outlook of Superwettability Membranes in Oil/Water Emulsions Separation (Adv. Mater. Interfaces 18/2021). Issue 18 (23rd September 2021) - Cai, Yahui; Shi, Sheldon Q.; Fang, Zhen; Li, Jianzhang
Abstract : Superwettability Membranes in Oil/Water Separation The discharge of a large amount of oily wastewater not only causes serious damage to the ecological environment, but also threatens human health. The special wettability functional separation membranes are an ideal choice to solve this problem. In article number 2100799, Yahui Cai, Jianzhang Li, and co‐workers review the separation membranes with hydrophobicity‐oleophilicity (or hydrophilicity‐underwater superoleophobicity) and smart, self‐repairing, self‐cleaning, and recycling properties.